A life more ordinary: A peer research method qualitative study of the Feeling Safe Programme for persecutory delusions. (8th August 2022) - Bond, Jessica; Kenny, Alexandra; Mesaric, Andreja; Wilson, Natalie; Pinfold, Vanessa; Kabir, Thomas; Freeman, Daniel; Waite, Felicity; Larkin, Michael; Robotham, Dan J.
Abstract: Background: The Feeling Safe Programme is a cognitive therapy developed to improve outcomes for individuals with persecutory delusions. It is theoretically driven, modular and personalised, with differences in therapeutic style and content compared with first‐generation cognitive behavioural therapy for psychosis. Objectives: We set out to understand the participant experience of the Feeling Safe Programme. Design: A qualitative study employing interpretative phenomenological analysis. Methods: Using a peer research approach, semi‐structured face‐to‐face interviews were conducted with six people who had received the Feeling Safe Programme as part of the outcome clinical trial. Results: Participants spoke of feeling 'unsafe' in their daily lives before the intervention. Openness to the intervention, facilitated by identification with the programme name, and willingness to take an active role were considered important participant attributes for successful outcomes. The therapist was viewed as a professional friend who cared about the individual, which enabled trust to form and the opportunity to consider new knowledge and alternative perspectives. Doing difficult tasks gradually and repeatedly to become comfortable with them was important for change to occur. The intervention helped people to do ordinary things that others take for granted and was perceived to produce lasting changes. Conclusions: The Feeling Safe Programme was subjectively experienced very positively by interview participants, which is consistent with the results of the clinical trial. The successful interaction of the participant and therapist enabled trust to form, which meant that repeated practice of difficult tasks could lead to re‐engagement with valued everyday activities.